Pemberdayaan Nelayan melalui Literasi Digital Kolaboratif: Nelayan Sekupang - Lestari, Dewi; Adi, Roni; Jufri, Muhammad (Penerbit Goodwood, 2025)
Purpose: This program aims to enhance the understanding of the Sekupang community, particularly fishers and small business owners, in utilizing digital technologies to support their economic activities. Through digital literacy training, participants are expected to access real-time market and weather information and leverage digital media to pro mote and market their products more effectively. Methodology/approach: The activity was conducted through a partnership between the Batam Institute of Technology and the Indonesian Traditional Fishermen’s Union. Participants consisted of fishers from Sekupang District, Batam City, Kepulauan Riau Province. The methods included lectures to introduce digital literacy concepts, group discussions to explore participants’ understanding, and hands-on simulations. A pre-test was administered to measure participants’ initial knowledge. Results/findings: The program improved digital literacy across five dimensions and was highly relevant to participants’ needs. More than 90% rated the training clear and useful, while 93% confirmed direct benefits such as using apps for weather and market information and utilizing social media and marketplaces to expand sales. The program successfully translated digital literacy into practical solutions for Sekupang’s fishers and households. Conclusions: This community service program successfully improved digital literacy among fishermen and housewives in Sekupang through relevant practical training, with participant satisfaction exceeding 90%, highlighting the importance of digital literacy for coastal communities. Limitations: The activity did not provide in-depth guidance on the practical application of digital literacy, leaving participants’ skills limited in some areas. Contribution: This program strengthened the foundational digital literacy skills of traditional fishers, supporting them in adopting digital technologies to enhance fishing practices and improve economic resilience.